2015
DOI: 10.1590/0103-8478cr20141128
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilidade fenotípica entre cultivares de pereiras europeias eporta-enxertos de marmeleiro

Abstract: <p>A cultura da pereira (<bold>Pyrus communis</bold>L.) possui grande potencial de expansão no sul do Brasil devido às condições climáticas e de solo. A carência de informações a respeito da(s) melhor(es) combinação(ões) de cultivares 'copa de pereiras europeias' e porta-enxertos de marmeleiro em relação à compatibilidade de enxertia é um dos fatores que tem limitado o cultivo de pera no país. A utilização de porta-enxertos de marmeleiros apresentam as vantagens de redução do vigor e rápida e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
5
2
Order By: Relevance
“…Regarding the scion cultivars, the obtained results differed from those of Machado et al (2015), who observed a greater growth of ' Abate Fetel', compared with 'Rocha', when grafted onto ' Adams'. However, Machado et al (2013) did not find differences between 'Rocha' and ' Abate Fetel' when grafted onto 'EMC'.…”
Section: Resultscontrasting
confidence: 85%
See 2 more Smart Citations
“…Regarding the scion cultivars, the obtained results differed from those of Machado et al (2015), who observed a greater growth of ' Abate Fetel', compared with 'Rocha', when grafted onto ' Adams'. However, Machado et al (2013) did not find differences between 'Rocha' and ' Abate Fetel' when grafted onto 'EMC'.…”
Section: Resultscontrasting
confidence: 85%
“…However, Machado et al (2013) did not find differences between 'Rocha' and ' Abate Fetel' when grafted onto 'EMC'. Although Machado et al (2015) observed good compatibility between ' Abate Fetel' and ' Adams', in the present study, the pear cultivar showed serious discontinuity in the bark and wood in the graft interface zone with quinces, which possibly negatively affected its growth (Almeida, 2018). These varying results may be a consequence of the different levels of graft compatibility.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Machado et al (2015) compared the trunk diameter with the continuity of the xylem vessels in the grafting region of six pear cultivars, on two quince rootstocks of the genus Cydonia, and observed that the greatest vigor is associated with the compatibility in the grafting region, with a continuous flow between the conducting vessels of the graft and the rootstock, which allowed the passage of the staining in the vascular bundles. Giacobbo et al (2007) evaluated the compatibility degree between quince of genus Cydonia and the pears 'Cascatense', 'Carrick' and 'Seleta', and observed that although 'Cascatense' showed a higher crown volume than the other cultivars, there was an incompatibility in its combination with quince due to a large difference in the trunk diameter between crown and rootstock.…”
Section: Resultsmentioning
confidence: 99%
“…rootstock, which provides plants with high vigor and slow production period (GIACOBBO et. al., 2007).The emergence of different quince clones (Cydonia oblonga) provided lower plant vigor and rapid fruiting (MILOSEVIC; MILOSEVIC, 2011); however, the quince root system is considered superficial and poorly expanded, with about 80% of the roots concentrated in the first 40 cm of depth (MACHADO, 2014).This characteristic of their root system gives the plants weak support to the soil, needing the installation of support systems and irrigation systems due to the greater stress of the plants in periods of low precipitation (ALMEIDA, 2014).…”
Section: Introductionmentioning
confidence: 99%